2014
DOI: 10.1371/journal.pone.0096489
|View full text |Cite
|
Sign up to set email alerts
|

Lower Fetuin-A, Retinol Binding Protein 4 and Several Metabolites after Gastric Bypass Compared to Sleeve Gastrectomy in Patients with Type 2 Diabetes

Abstract: BackgroundBypass of foregut secreted factors promoting insulin resistance is hypothesized to be one of the mechanisms by which resolution of type 2 diabetes (T2D) follows roux-en-y gastric bypass (GBP) surgery.AimTo identify insulin resistance-associated proteins and metabolites which decrease more after GBP than after sleeve gastrectomy (SG) prior to diabetes remission.MethodsFasting plasma from 15 subjects with T2D undergoing GBP or SG was analyzed by proteomic and metabolomic methods 3 days before and 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…The reason for these findings is that duodenal exclusion might have a significant role in the treatment diabetes apart from weight reduction. A recent study comparing LSG and RYGB identified some duodenal factors that are possibly related to duodenal exclusion supported the duodenal exclusion theory [30]. In this study, the patients who received gastric bypass had significant lower HbA1c and LDL levels than did those who received LSG at 5 years after surgery.…”
Section: Discussionsupporting
confidence: 73%
“…The reason for these findings is that duodenal exclusion might have a significant role in the treatment diabetes apart from weight reduction. A recent study comparing LSG and RYGB identified some duodenal factors that are possibly related to duodenal exclusion supported the duodenal exclusion theory [30]. In this study, the patients who received gastric bypass had significant lower HbA1c and LDL levels than did those who received LSG at 5 years after surgery.…”
Section: Discussionsupporting
confidence: 73%
“…The effect of bariatric surgery on the circulating levels of fetuin-A remains to be fully elucidated. A fall in levels has been reported in the immediate postoperative period [139] and up to 16 months after surgery [146]. However, one study reported a rise in serum fetuin-A levels in patients with NASH 4 weeks postoperatively [145], which returned to preoperative levels at 6 months.…”
Section: Insulin Resistancementioning
confidence: 98%
“…Retinal-binding protein 4 (RBP4) and fetuin-A are two further insulin-blunting mediators that have been shown to be reduced following bariatric procedures [138][139][140]. RBP4 is a vitamin A transport protein secreted by adipocytes and hepatocytes that has been shown to induce insulin resistance in muscle, liver and fat [141].…”
Section: Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In research related to T2D, Jullig et al used iTRAQ labeling of plasma to identify factors that favor resolution of T2D in subjects undergoing roux‐en‐y gastric bypass (GBP) surgery when compared with sleeve gastrectomy ( n = 15) . Culnan and co‐workers also considered changes in the plasma proteome associated with gastric by‐pass surgery .…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%